2002
DOI: 10.1073/pnas.142627899
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of CIA/ASF1 as an interactor of bromodomains associated with TFIID

Abstract: General transcription initiation factor IID (TFIID) plays a central and critical role in transcription initiation from both naked and chromatin templates. Although interaction between several DNAbinding proteins and TFIID were identified and well characterized, functional linkage between TFIID and chromatin factors has remained to be elucidated. Here we show the identification and characterization of human CIA͞hASF1 (identified previously as a histone chaperone) as an interactor of two tandem bromodomain modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 63 publications
(64 reference statements)
4
79
0
Order By: Relevance
“…The histone chaperone ASF1 has been shown previously to bind to bromodomains (29), but the mode of interaction with the CBP bromodomain is quite distinct from that observed with the CCG1 bromodomain (30). We find that the interaction between the CBP bromodomain and ASF1 and the interaction between ASF1 and histones promoted histone acetylation on free histones.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The histone chaperone ASF1 has been shown previously to bind to bromodomains (29), but the mode of interaction with the CBP bromodomain is quite distinct from that observed with the CCG1 bromodomain (30). We find that the interaction between the CBP bromodomain and ASF1 and the interaction between ASF1 and histones promoted histone acetylation on free histones.…”
Section: Discussionsupporting
confidence: 41%
“…5A). ASF1A previously has been shown to bind to the bromodomain of the CCG1 protein (29). Therefore, we wondered whether the bromodomain of CBP is important for the interaction with ASF1.…”
Section: Autoacetylation Of Cbp Is Required For the Bromodomain Intermentioning
confidence: 98%
“…However, no direct interaction between Asf1 and Gcn5 has been reported so far. Asf1 has been reported to bind to the bromodomain-containing proteins Brd1 and Brd2 in yeast and Brahma in Drosophila (24,25). As Gcn5 does contain a bromodomain (26), it may be a potential binding partner of Asf1 that merits further investigation in the future.…”
Section: Asf1 Promotes Acetylation Of Free H3mentioning
confidence: 98%
“…First, mutation of the yeast asf1 gene results in the suppression of S-phase-specific histone genes activation (Sutton et al 2001). Second, it was shown that ASF1 interacts with bromodomain-containing subunits of TFIID (Munakata et al 2000;Chimura et al 2002).…”
Section: Asf1 Interacts With the Brahma Complex Genes And Development 2623mentioning
confidence: 99%